Ab initio simulation of functionalized β12 borophene - Ledur, Cristian Mafra; Darold, Marcella Wayss; Gündel, Eduardo; Fagan, Solange Binotto (Disciplinarum Scientia | Naturais e Tecnológicas, 2021)
In this work we evaluated the structural and electronic properties of C-doped and COOH-functionalized β12 borophene through ab initio simulations using the density functional theory (DFT). β12 borophene is a stable 2D nanomaterial and composed only by B atoms, with promising applications specially for the electronic industry. The substitutional C-doped β12 borophene is chemically favorable with a strong hybridization of carbon-boron energy levels. The COOH-functionalization on β12 borophene presents high energy adsorption (around 3.2 eV). The studied functionalizations show metallic electronic properties in the resulting systems, as well as observed for pristine β12 borophene.